Assessment of the Repellent Efficacy of Allomones against the Larval Stages of Brown Dog Tick - Bhoopathy, Dhivya; jeyathilakan, Narayanaperumal; Arunkumar, Selvarayar; Mangalagowri, Angappan; Selvaraj, Palanisamy (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
Ticks and tick-borne diseases are a major threat to livestock and companion animals. Hematophagous ticks transmit a variety of pathogens along with the direct effects such as tick worry and skin damages. Acaricides has been the mainstay in fighting off ticks until the emergence of resistance which forced researchers to look out for alternate tick control strategies. Allomones (non-host semiochemicals-NHC’s) are semiochemicals which benefit the host and deter the pests. The NHC’s in certain breeds of dogs have been elucidated and their function has been decoded. The current study was attempted in formulating a sustained release of these allomones using vapour patches and assessing their efficacy by in-vitro assay. It was found that allomones tested had a strong repellent effect on Rhipicephalus sanguineus comparable to that of the commercial repellent DEET.